2020
DOI: 10.1155/2020/2626584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Analysis of Polyadenylation Sites in Fast and Slow Muscles

Abstract: Many increasing documents have proved that alternative polyadenylation (APA) events with different polyadenylation sites (PAS) contribute to posttranscriptional regulation. However, little is known about the detailed molecular features of PASs and its role in porcine fast and slow skeletal muscles through microRNAs (miRNAs) and RNA binding proteins (RBPs). In this study, we combined single-molecule real-time sequencing and Illumina RNA-seq datasets to comprehensively analyze polyadenylation in pigs. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Post-transcriptional modification events of precursor-messenger RNA (pre-mRNA), including alternative splicing (AS) and alternative polyadenylation (APA), have attracted an increasing interest ( Baralle & Giudice, 2017 ; Di Giammartino, Nishida & Manley, 2011 ; Gruber & Zavolan, 2019 ; Kornblihtt et al, 2013 ; Wang et al, 2015 ). In livestock, accumulated evidence suggests that AS ( Fang et al, 2020 ; Leal-Gutierrez, Elzo & Mateescu, 2020 ; Xiang et al, 2018 ; Yuan et al, 2021 ) and APA ( Deng et al, 2020 ; Jin et al, 2021 ) could contribute to the formation of important economic traits. For example, both AS ( Motter, Corva & Soria, 2021 ) and APA ( Nattrass et al, 2014 ) in calpastatin ( CAST ) were associated with meat tenderness in beef.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-transcriptional modification events of precursor-messenger RNA (pre-mRNA), including alternative splicing (AS) and alternative polyadenylation (APA), have attracted an increasing interest ( Baralle & Giudice, 2017 ; Di Giammartino, Nishida & Manley, 2011 ; Gruber & Zavolan, 2019 ; Kornblihtt et al, 2013 ; Wang et al, 2015 ). In livestock, accumulated evidence suggests that AS ( Fang et al, 2020 ; Leal-Gutierrez, Elzo & Mateescu, 2020 ; Xiang et al, 2018 ; Yuan et al, 2021 ) and APA ( Deng et al, 2020 ; Jin et al, 2021 ) could contribute to the formation of important economic traits. For example, both AS ( Motter, Corva & Soria, 2021 ) and APA ( Nattrass et al, 2014 ) in calpastatin ( CAST ) were associated with meat tenderness in beef.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is unlikely to obtain the full-length transcripts and quantify the transcripts by RNA-seq because it is difficult to assemble full-length transcripts based on short reads and to exactly assign a short read to a certain transcript ( Kovaka et al, 2019 ), which hamper the discovery of post-transcriptional events. The third-generation sequencing technology, such as PacBio isoform sequencing (Iso-Seq), which can directly produce full length transcripts ( Rhoads & Au, 2015 ), providing an opportunity to discover novel genes and novel isoforms ( Au et al, 2013 ; Beiki et al, 2019 ; Chen et al, 2017 ; Karlsson & Linnarsson, 2017 ) and to investigate the transcriptome complexity in mammals ( Deng et al, 2020 ; Li et al, 2018b ). In addition, the results from the previous study suggested that integrative analysis of Iso-Seq and RNA-seq data could accurately quantify the abundance of transcripts ( Chao et al, 2019 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pig GCs, cellular-FLICE like inhibitory protein (cFLIP) and estrogen receptor beta (ER beta) have two alternative splicing isoforms and participate in follicular development ( LaVoie et al, 2002 ; Matsuda-Minehata et al, 2005 ). APA is associated with the rapid and slow porcine muscle development ( Deng et al, 2020 ). In a word, there are few reports on the occurrence and function of gene AS and APA in GCs and the follicular development of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is unlikely to obtain the fulllength transcripts and quantify the transcripts by RNA-seq because it is difficult to assemble fulllength transcripts based on short reads and to exactly assign a short read to a certain transcript (Kovaka et al 2019), which hamper the discovery of post-transcriptional events. The thirdgeneration sequencing technology, such as PacBio isoform sequencing (Iso-Seq), which can directly produce full length transcripts (Rhoads & Au 2015), providing an opportunity to discover novel genes and novel isoforms (Au et al 2013;Beiki et al 2019;Chen et al 2017;Karlsson & Linnarsson 2017) and to investigate the transcriptome complexity in mammals (Deng et al 2020;Li et al 2018b). In addition, the results from the previous study suggested that integrative analysis of Iso-Seq and RNA-seq data could accurately quantify the abundance of transcripts (Chao et al 2019;Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%